Master poets, ritual masters: The art of oral composition among the Rotenese of Eastern Indonesia - J. Fox, James (ANU Press, 2016)
This is a study in oral poetic composition. It examines how oral poets compose their recitations. Specifically, it is a study of the recitations of 17 separate master poets from the Island of Rote recorded over a period of 50 years. Each of these poets offers his version of what is culturally considered to be the 'same' ritual chant. These compositions are examined in detail and their oral formulae are carefully compared to one another. Professor James J. Fox is an anthropologist who carried out his doctoral field research on the Island of Rote in eastern Indonesia in 1965-66. In 1965, he began recording the oral traditions of the island and developed a close association with numerous oral poets on the island. After many subsequent visits, in 2006, he began a nine-year project that brought groups of oral poets to Bali for week-long recording sessions. Recitations gathered over a period of 50 years are the basis for this book.